Frontier groundwater investigations in the west Kimberley (Fitzroy) Region: preliminary assessment of groundwater resource potential and the salinity hazard to proposed irrigation developments. Issue 1 (1st December 2016) - Hoare, Alastair; Tan, Kok Piang; Stocker, Celine; Lawrie, Ken; Halas, Larysa; Mueller, Norman; Symington, Neil; Brodie, Ross C.; Tingey, Wayne; Brodie, Ross S.; Magee, John
Abstract : A regional reconnaissance AEM survey in the west Kimberley region (lower Fitzroy River valley and May-Meda Catchments) has successfully mapped the extent of regional Canning Basin aquifers (e.g. Pool Sandstone, Grant Group and Erskine Sandstone) confirming these as significant potential groundwater resources. The survey has successfully mapped a multi-layered hydrostratigraphy to depths of 400m (in resistive areas), also revealing significant tectonics manifested as large scale basin-scale tilting of stratigraphy and more localised folding and faulting. The survey also mapped other key objectives including: the seawater intrusion (SWI) interface for the lower Fitzroy River valley and the May and Meda River Catchments; river flush zones along the Fitzroy, May and Meda Rivers; groundwater salinity variations and potential salt stores in the shallow alluvium of these rivers and proposed irrigation areas. River-parallel surveys also identified reaches of the May and Meda Rivers with direct contact between the rivers and underlying regional aquifers of the Pool Sandstone and Grant Group. These reaches are areas of potential recharge, and/or groundwater discharge, with the AEM used to target hydrochemical investigations, drilling and aquifer testing. The AEM data reveal more complex relationships between perennial in-stream pools along the Fitzroy River, underlying aquifers, tectonics, and river alluvium. AEM survey design incorporated time series analysis of surface water availability through time (Water Observations from Space (WOfS)) derived using the Australian Geoscience Data Cube (AGDC). This has facilitated investigations of surface-groundwater interaction through ensuring the AEM transects coincide with permanent water holes and river reaches considered to be potentially sustained by groundwater discharge. The AEM data provide a framework for hydrogeological process understanding, while the knowledge generated in this project will inform water resource allocation planning, help assess risks to culturally and environmentally sensitive riverine ecosystems, and de-risk investment in agriculture and water infrastructure more broadly.